Pengaruh Kepemimpinan dan Pengalaman Kerja terhadap Kinerja Karyawan pada PT Mega Auto Central Finance Jakarta Barat - Kumoro, Mei Muhamad Daru (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2023)
This research aims to determine the leadership performance and work experience on PT Mega Auto Central Finance employees, both partially or concurrently. This research uses quantitative methods with data collection techniques through distributing questionnaires. The sample in this research used the “slovin sample formula” which was obtained from 80 employees of PT Mega Auto Central Finance. The use of analytical methods is namely multiple linear regression analysis, with the analysis of the coefficient of determination (R2), t test, and F test. The results of multiple linear regression analysis are the equation Y = 12.020 + 0.414X1 + 0.210X2+e, so that a coefficient of determination of 0.414 or 41.4% is obtained, which means that the coefficient of determination of employee performance variables is explained by leadership and work experience variables, while the remaining 58,6% is explained by other variables outside the research. The results of the t test show that the leadership variable (X1) obtained t count 4.104 > t table 1.990 with sig 0.000 < 0.05 then Ha1 is accepted and Ho1 is rejected, work experience variable (X2) t count 2.087 > t table 1.990 with sig 0.040 < 0.05 then Ha2 is acceptef and Ho2 is rejected. Therefore, the leadership variable (X1) has a partial effect on employee performance variables (Y), and also, work experience variable (X2) has a partial effect on employee performance (Y). The results of the F test show that F count is 28.950 > F table 3.12 and a significance of 0.000 <0.05, where Ho is rejected and Ha is accepted, which means that there is a concurrently significant effect between leadership variables (X1) and work experience (X2) on employee performance variable (Y).